Liberalisme dan Kritisisme dalam Pendidikan Modern: Suatu Analisis Filosofis Pendidikan Islam - Maghfirah, Maghfirah; Walidin AK, Warul; Silahuddin, Silahuddin (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
Modern education today cannot be separated from the influence of two main schools of Western philosophy, namely liberalism and criticalism. Liberalism emphasizes individual freedom and autonomy of thought, while criticalism focuses on rationality and reflective thinking. On the other hand, Islamic education has a different philosophical foundation to these paradigms, focusing on the integration of science with moral and spiritual values. This research aims to integrate liberalism, criticalism, and Islamic education in a holistic philosophical framework of analysis. This research uses a qualitative approach with a library research design and philosophical analysis involving the dimensions of ontology, epistemology, and axiology in the philosophy of education. The data used are philosophical texts, books, journal articles, and other relevant documents. Data sources were obtained through purposive sampling from credible literature, both in print and electronic form. Data collection techniques were conducted through literature study, while data analysis used qualitative techniques with the stages of data reduction, data presentation, and conclusion drawing. The results show that the integration of liberalism and criticalism values in Islamic education can enrich the learning process without sacrificing the basic principles of Islam, so that Islamic education can remain relevant to the times and form individuals who are intellectually intelligent and have noble character.